2018
DOI: 10.3390/cells7090142
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Prevents In Vitro Transforming Growth Factor-β1-Induced Fibroblast to Myofibroblast Transition: Involvement of Vascular Endothelial Growth Factor (VEGF)-A/VEGF Receptor-1-Mediated Signaling †

Abstract: The antifibrotic potential of platelet-rich plasma (PRP) is controversial. This study examined the effects of PRP on in vitro transforming growth factor (TGF)-β1-induced differentiation of fibroblasts into myofibroblasts, the main drivers of fibrosis, and the involvement of vascular endothelial growth factor (VEGF)-A in mediating PRP-induced responses. The impact of PRP alone on fibroblast differentiation was also assessed. Myofibroblastic phenotype was evaluated by confocal fluorescence microscopy and western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 105 publications
8
55
0
Order By: Relevance
“…In this regard, Platelet-Rich Plasma (PRP)-defined as a plasma fraction with a concentration of platelets above baseline levels and representing a source of numerous biologically active molecules-may offer promising perspectives [30]. Indeed, many in vitro and in vivo studies have demonstrated the anti-fibrotic potential of this blood product in different tissues [31][32][33][34][35][36][37][38], including skeletal muscle [30,[39][40][41][42][43][44][45][46], and have indicated the fibroblast-myofibroblast transition as the cell process target of its action [31][32][33]36,38,44,47,48]. Furthermore, the positive contribution of PRP to skeletal muscle regeneration has been demonstrated either in vivo or in vitro, thanks to its capability to promote the myogenic program [30].…”
Section: Prp As An Anti-fibrotic Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Platelet-Rich Plasma (PRP)-defined as a plasma fraction with a concentration of platelets above baseline levels and representing a source of numerous biologically active molecules-may offer promising perspectives [30]. Indeed, many in vitro and in vivo studies have demonstrated the anti-fibrotic potential of this blood product in different tissues [31][32][33][34][35][36][37][38], including skeletal muscle [30,[39][40][41][42][43][44][45][46], and have indicated the fibroblast-myofibroblast transition as the cell process target of its action [31][32][33]36,38,44,47,48]. Furthermore, the positive contribution of PRP to skeletal muscle regeneration has been demonstrated either in vivo or in vitro, thanks to its capability to promote the myogenic program [30].…”
Section: Prp As An Anti-fibrotic Agentmentioning
confidence: 99%
“…In particular, we focused the attention on the GJIC. The experimental model to evaluate fibroblast to myofibroblast transition has been previously validated [23,24,48,[55][56][57] and consists in the culture of the cells in low serum conditions in the presence of TGF-β1. The treatment with PRP was also conducted as previously reported [48,57,58].…”
Section: Gap Junction Intercellular Communication (Gjic)mentioning
confidence: 99%
“…10 Among these materials, platelet-rich plasma (PRP) can be defined as a plasma fraction with platelet concentration higher than the baseline concentration in whole blood and that has antifibrotic action. 11 Autologous fat grafts have been commonly used to prevent the epidural adhesion after lumbar laminectomy. 3,12 Collagen dural matrix (DuraGen) is a chemical cross-linked type 1collagen foam made from bovine tendon and has been suggested to reduce fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is likely that in the context of L‐PRF, the effect of released TGF‐β on NHGFs is counteracted by other molecules released from the membrane. Notably, a recent study demonstrates that L‐PRF‐derived VEGF‐A can attenuate TGF‐β signalling and myofibroblastic differentiation (Chellini et al, 2018).…”
Section: Discussionmentioning
confidence: 99%